Evaluation of outcomes of replantation, acute repair, and revision amputation for digital amputations: A 5-year retrospective study - Boynuyoğun, Etkin; Tosun, Hatice; Bakkaloğlu, Yağmur Nahide; Cakaroğlu, Melih; Koçer, Uğur (Acta Medica, 2025)
Objective: This study aims to objectively assess postoperative hand function by categorizing patients into three groups: replantation, acute stump repair, and revision amputation after unsuccessful replantation. Additionally, functional evaluation questionnaires were used to assess patient satisfaction among these groups. Materials and Methods: A total of 150 patients were included in the study, 50 patients in each group. Patients’ age, gender, comorbidities, dominant hand, the level of amputation, injured fingers and the mechanism of trauma were recorded. Afterwards, the patients were administered the EQ-5D-5L quality of life scale, the Quick DASH test, the Cold Intolerance and the Semmes–Weinstein monofilament test. Results: A total of 167 finger amputations in 150 patients, 82% of whom were male and 18% were female. Their ages ranged from 19 to 92, and the mean age was 45.5. The mean score in patients who underwent acute repair was higher than in patients who underwent replantation and revision amputation in the EQ-5D-5L scale, the score of the replantation group was minimally lower than in the other two groups for the Quick DASH scoring, sensory results were minimally decreased in the replantation group compared to the revision amputation and acute repair groups. Cold intolerance was reported in 39% of replantation cases compared to 30.3% in revision amputation and 20% in acute repair (p<0.05). Conclusion: Digital amputations were most frequently seen in male patients, in the 3rd finger and at the level of the distal interphalangeal joint. According to the EQ-5D-5L scale, Semmes-Weinstein monofilament test and cold intolerance assessment, the results were worse in the replantation group compared to the other two groups, and better in the Quick DASH score. The advantages and disadvantages of possible treatment options should be explained to the patient and their expectations should be taken into consideration in choosing the treatment for finger amputations.